The Afterlife Project - Weed, Tim (Podium Publishing, 2025)
"With humanity facing imminent extinction, Centauri Project scientists use technology originally designed for interstellar travel to send a test subject ten millennia into Earth's future. Marooned in an uninhabited wilderness, microbiologist Nicholas Hindman searches for evidence of remnant populations. He has a protocol to follow and is determined to do so to the bitter end--though he knows he's probably searching in vain, stranded on an empty planet silently orbiting the sun. Meanwhile, back in 2068 AD, a devastating hyperpandemic has quelled all talk of interstellar travel and thrown the future of humanity into grave doubt. Four surviving members of the Centauri team board a vintage solar-powered sailing yacht for a harrowing journey in search of a second test subject. Their destination is a small volcanic island north of Sicily rumored to harbor that rarest of creatures: a woman capable of getting pregnant, thereby ensuring this generation of Homo sapiens isn't the last. But first they must make it halfway across the post-apocalyptic globe, risking heatwaves, oceanic megastorms, murderous gangs, deranged cult leaders, a volcanic eruption, and the dangerous microbes that continue to circulate through the planet's atmosphere."--Amazon.